2016
DOI: 10.1016/j.apjtm.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of Irbesartan on occurrence of ventricular arrhythmias in rats with myocardial ischemia through connexin43 (cx43)

Abstract: Irbesartan can inhibit the injury of H9c2 cardiomyocytes and the decreased expression of Cx43 that are induced by the ischemic myocardial infarction. Irbesartan can also improve the reconstruction of Cx43 in rats with ischemic myocardium to inhibit the myocardial infarction-induced arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Lindsey et al ( 18 ) reported that the positive expression of Cx43 in model of myocardial infarction was significantly reduced, and the expression level of Cx43 protein was significantly lower than that of the control group, but the expression of Cx43 mRNA was not altered significantly. Results of this study showed that the distribution of Cx43 protein and the level of Cx43 mRNA and protein in rabbits after myocardial infarction were significantly decreased (P<0.05), suggesting that connexins were reconstructed after myocardial infarction, which is consistent with previous studies ( 19 ). After treatment with metoprolol, levels of Cx43 mRNA and protein in cardiomyocytes were significantly increased, suggesting that metoprolol can play a role in improving cardiac remodeling after myocardial infarction by regulating the expression of Cx43.…”
Section: Discussionsupporting
confidence: 91%
“…Lindsey et al ( 18 ) reported that the positive expression of Cx43 in model of myocardial infarction was significantly reduced, and the expression level of Cx43 protein was significantly lower than that of the control group, but the expression of Cx43 mRNA was not altered significantly. Results of this study showed that the distribution of Cx43 protein and the level of Cx43 mRNA and protein in rabbits after myocardial infarction were significantly decreased (P<0.05), suggesting that connexins were reconstructed after myocardial infarction, which is consistent with previous studies ( 19 ). After treatment with metoprolol, levels of Cx43 mRNA and protein in cardiomyocytes were significantly increased, suggesting that metoprolol can play a role in improving cardiac remodeling after myocardial infarction by regulating the expression of Cx43.…”
Section: Discussionsupporting
confidence: 91%
“…Reperfusion injury potentiates membrane permeability of cardiomyocytes and elevates myocardial injury marker levels in serum. The severity of myocardial tissue injury is correlated with CK-MB and cTnI levels [ 13 , 14 ]. Recent findings show that a variety of components from plants, such as malvidin, contribute to cardioprotective effects against isoproterenol-induced myocardial infarction in rats [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis showed that there was a significant positive correlation between CX43 and VFT after MI, that is, the expression of CX43 decreased, the VFT decreased, and the risk of arrhythmia increased. Since improving the expression of CX43 can effectively reduce the occurrence of arrhythmia after MI [ 18 ]. Therefore, further research on the molecular mechanism of regulating connexin could provide ideas for the prognostic treatment of MI.…”
Section: Discussionmentioning
confidence: 99%